What is the Relationship between Cognitive and Non-Cognitive Skills and the Adoption of Risk Behavior in Peru? - Lavado, Pablo (2015)
For many years, research has dealt with the relationship between the adoption of risk behaviors by teenagers and factors related to the family or the environment, ignoring other factors such as teenagers’ own cognitive or non-cognitive skills. This study seeks to demonstrate the relationship between these two variables and ascertain whether adolescents’ cognitive and non-cognitive skills are negatively associated with the consumption of tobacco and alcohol and the early initiation of sexual activity. The investigation used Peru’s Young Lives database and employed two estimation methods: fixed effects and instrumental variables. The results show that the relationship between risk behaviors and cognitive and non-cognitive skills is negative. That is, adolescents with higher levels of intelligence, self-esteem, and self-efficacy are less likely to engage in risky behaviors.